PENGARUH HARDINESS TERHADAP WORK ENGAGEMENT PADA KARYAWAN PT. TELKOM INDONESIA WITEL JAMBI: THE EFFECT OF HARDINESS ON WORK ENGAGEMENT IN OUTSOURCING EMPLOYEES OF PT TELKOM INDONESIA WITEL JAMBI - Zahran, Ariq; Rahim, Beny; Nofrianda, Rion (Jurnal Psikologi Jambi, 2024)
ABSTRACT Introduction Human resources (HR) are productive individuals who work as the driving force of an organization. In the world of work, employees are required to work optimally and involve themselves in work or Work Engagement. Purpose This study aims to see the effect of hardiness on work engagement in outsourcing employees of PT Telkom Indonesia Witel Jambi. Method This research uses quantitative methods with a correlational approach, the sampling technique used is purposive sampling technique with data collection techniques surveys. The population in this study were outsourced employees of PT Telkom Indonesia Witel Jambi. Result Descriptive data shows that most outsourced employees are male and in terms of age, employees in the age of 20-30 are the most respondents. The analysis shows the effect of Hardiness on Work Engagement has a positive influence (r square = 0.246, Sig = 0.000). Conclusions A positive influence indicates that outsourcing employees of PT. Telkom Indonesia Witel Jambi feel they have resilience in dealing with work pressure and workload. Sufficient resilience has an influence in involving themselves in doing work. Keywords: Hardiness, Work Engagement, Outsourcing ABSTRAKPendahuluan Sumber daya manusia adalah individu produktif yang bekerja sebagai penggerak suatu organisasi. Dalam dunia kerja, karyawan dituntut untuk bekerja dengan maksimal dan melibatkan dirinya. Penelitian ini bertujuan untuk melihat Pengaruh hardiness terhadap work engagement pada karyawan outsourcing PT. Telkom Indonesia Witel Jambi. Metode Penelitian ini menggunakan metode kuantitatif dengan pendekatan korelasional, teknik sampling yang digunakan yaitu teknik purposive sampling. Populasi pada penelitian ini adalah karyawan outsourcing PT. Telkom Indonesia Witel Jambi. Hasil Data deskriptif menunjukkan sebagian besar karyawan outsourcing berjenis kelamin laki-laki dan dari segi usia, karyawan di usia 20-30 menjadi responden terbanyak. Analisis menunjukkan pengaruh hardiness terhadap work engagement memiliki pengaruh positif (R 2 = 0,246, Sig =0,000). Kesimpulan Pengaruh yang positif dan siginifikan menunjukkan bahwa karyawan outsourcing PT. Telkom Indonesia Witel Jambi merasa memiliki ketahanan dalam menghadapi tekanan kerja dan beban kerja. Ketahanan diri yang cukup memberikan pengaruh dalam melibatkan dirinya. Kata kunci : Hardiness, work engagement, outsourcin